Metode Storytelling: Peningkatkan Motivasi Perilaku Antikorupsi - Lestyowati, Jamila (Integritas : Jurnal Antikorupsi, 2020)
The study aims to analyze storytelling methods to improve student’s understanding and motivate participants about anticorruption. This study was classroom action research that applied to Anticorruption subject of basic training. The action’s recipients were participants batch IV with 61 persons and the action subject was instructor. Data collection used observation, questionnaires and interviews while analysis used qualitative descriptive including reduction, presentation, and verification of data. The results showed that the storytelling method was a method that made participants active, increased learning motivation, improved learning outcomes and in accordance with the learning objectives through trustworthy and honest behavior.